PERUBAHAN VOLUME TUMOR POST-RADIASI EKSTERNA PADA PASIEN KANKER NASOFARING - Aidilawarti K. S.; Guntur Winarno; Asumsie Tarigan; Moh. Haris (Perhimpunan Radiografer Indonesia (PARI), 2019)
Introduction: The radiotherapists provides fractional treatment effectively and efficiently. The expected radiation response can be achieved for tumor volume change so that the principle in radiotherapy is to kill as many cancer cells as possible. However, due to the prognostic factors that may affect the radiation response such as Epstein-Barr Virus, TNM stage system, primary tumor, patient age, sex, type of treatment, and histopathology. Objective: This study is intended to analyze changes in the volume of external post-radiation tumors in nasopharyngeal cancer patients. Methods: This study is a descriptive quantitative study to determine changes in tumor volume from pro-radiation to post-radiation in patients with nasopharyngeal cancer. The sample used was the secondary data which belongs to Radiotherapy Installation at Dharmais Cancer Hospital Jakarta in patients with nasopharyngeal cancer in 2017. The study sample was taken on subjects who meet the criteria of inclusion and exclusion. Results: From the 51 study samples, the results are obtained based on stages, post-radiation tumor volume changes from stage II, III, and IV by 206.56643cc, 135.81397cc, and 168.83302cc. By sex, post-radiation tumor volume changes of male and female sexes were 174,18946cc and 176,02196cc. By age, post-radiation tumor volume changes in the age group 20-39 years, 40-49 years and> 50 years of 183.42215cc, 175.36875cc, and 166.95548cc. Conclusion: It can be concluded that the largest tumor volume change which leads to radiation effectiveness and better prognosis based on stage is at stage II, based on sex is on female gender, and by age was in the age group of 20-39 years. Keywords: Tumor volume change, Post-radiation, Nasopharyngeal cancer